Women's Perceived of Mammography in National Center of Early Detection of Breast Cancer at Baghdad Medical City - Bayda'a Abdul Kareem (Kufa Journal for Nursing Sciences)
Background: breast cancer is the most commonly diagnosed cancer among women worldwide, although breast screening with Mammography can reduce mortality in breast cancer. Women perceived fear, barriers, benefit, and self-efficacy can affect their decision to participation in Mammography screening.